1999
DOI: 10.1007/s002239900726
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Androgen Levels in Elderly Males

Abstract: To clarify the relationship of sex male hormones and bone in men, we studied in 140 healthy elderly men (aged 55-90 years) the relation between serum levels of androgens and related sex hormones, bone mineral density (BMD) at different sites, and other parameters related to bone metabolism. Our results show a slight decrease of serum-free testosterone with age, with an increase of follicle stimulating hormone (FSH) and luteinizing hormone (LH) in a third of the elderly subjects studied. BMD decreased significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 19 publications
3
19
0
1
Order By: Relevance
“…Low testosterone levels may be a risk factor for cardiovascular disease [21] and the low BMD might reflect its association with BMD and risk of mortality. Low testosterone may also be involved in the stimulation of biologic response to vitamin D in the target organs, such as intestine and bone [22], although a more recent study has shown that sex male hormones are not correlated with the decrease in hip BMD [23]. The findings raise questions regarding the role of androgens in cardiovascular risk and lipid profile and their possible association with BMD.…”
Section: Discussionmentioning
confidence: 95%
“…Low testosterone levels may be a risk factor for cardiovascular disease [21] and the low BMD might reflect its association with BMD and risk of mortality. Low testosterone may also be involved in the stimulation of biologic response to vitamin D in the target organs, such as intestine and bone [22], although a more recent study has shown that sex male hormones are not correlated with the decrease in hip BMD [23]. The findings raise questions regarding the role of androgens in cardiovascular risk and lipid profile and their possible association with BMD.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous studies investigated the putative physiological relationship between circulating levels of 25OHD 3 /1,25(OH) 2 D, the activity of VDR and VD metabolizing enzymes, and serum testosterone and estradiol levels in both animals and humans (Tanaka et al 1976, Hyldstrup et al 1984, Small et al 1984, Hochberg et al 1985, Krabbe et al 1986, Sonnenberg et al 1986, Hagenfeldt et al 1992, Morley et al 1993, Inpanbutr et al 1996, Otremski et al 1997, Rapado et al 1999, Kinuta et al 2000, van Abel et al 2002, Braga et al 2002, Van Cromphaut et al 2003, Echchgadda et al 2004, Valimaki et al 2004, Kastelan et al 2009, Fleet & Schoch 2010, Krishnan et al 2010a, 2010b, Meng et al 2010, Pilz et al 2011, Ramlau-Hansen et al 2010, Wehr et al 2010, Ceglia et al 2011, Foresta et al 2011, Lundqvist et al 2011, Lee et al 2012. It has been shown that estrogen promotes the two-step activation of cholecalciferol to 1,25(OH) 2 D 3 and reinforces a positive effect on calcium homeostasis through a direct stimulatory effect on intestinal calcium absorption.…”
Section: Vd Regulates Biosynthesis Of Estradiol and Testosteronementioning
confidence: 99%
“…In general, correlations between bone mass and serum androgen concentrations in adult men have been either weak or insignificant [17,42,48]. Furthermore, many of the various clinical trials examining androgen therapy have been unable to demonstrate robust effects on bone mass, including treatment with anabolic steroids [11].…”
Section: Introductionmentioning
confidence: 99%